Timing and pathogenesis of heart conduction disorders during transcatheter aortic valve implantation: data of intraoperative Holter monitoring - A. A. Baranov; O. A. Bystritskaya; E. S. Zamaraeva; A. G. Badoyan; D. A. Khelimsky; A. Yu. Tsydenova; I. S. Peregudov; A. G. Filippenko; M. A. Yusupova; S. V. Maingart; A. N. Fedorchenko; O. V. Krestyaninov (Российский кардиологический журнал)
Aim. To evaluate the timing and relationship of heart conduction disorders with various surgical steps of transcatheter aortic valve implantation (TAVI) using intraoperative Holter monitoring.Material and methods. This prospective observational study included 60 patients with high risk of atrioventricular (AV) conduction abnormalities who underwent TAVI for severe aortic stenosis. Intraoperative heart rhythm assessment was performed using continuous Holter monitoring. After the procedure, cardiac rhythm recording was continued for the next 24 h. The target time intervals of the main surgical steps were then compared with conduction disorders (transient and/or persistent) identified (first-degree AV block, complete AV block, right and left bundle branch blocks).Results. Newly diagnosed conduction disorders were noted in 85,3% of patients. In 31,2% of patients, conduction disorders were noted before bioprosthetic valve implantation (positioning of guidewire, balloon valvuloplasty), in 23,4% — at the stage of bioprosthetic valve implantation, and in 31,5% — immediately after the balloon postdilation. The transient course was most characteristic of complete AV block, the resolution of which in the postoperative period was noted in 62,5% of cases. First-degree AV block and left bundle branch block persisted before discharge from the hospital in 71,4% and 65% of cases, respectively. Among transient cardiac conduction disturbances, first-degree AV block had the longest duration, the median time to resolution of which was 420 min.Conclusion. About a third of heart conduction disorders in TAVI occur before bioprosthetic valve implantation. The most common heart conduction disorder after TAVI is new-onset complete left bundle branch block, which in most cases is persistent and remains until the patient is discharged from the hospital. Intraoperative heart rhythm monitoring after TAVI can be an important tool for assessing and predicting various heart conduction disorders, as well as determining the optimal postoperative patient management strategy.